Natural oil-based sustainable materials for a green strategy - Balo, Figen; Aksakal, Berrak; Sua, Lutfu S.; Mahmat, Zeliha (Wiley Blackwell, 2021)
Utilization of sustainable resources is significant, considering the effects of fossil-sourced plastics. Using sustainable sources, such as plant oils, for biobased plastic fabrication proposes the benefits of lesser dependency on petroleum-based energy resources and sustainability. Natural epoxidized oils are additives to replace and strengthen fossil plastics. Epoxidized vegetable oils attracts more interest recently, particularly the plastic sector as they become available, economicaly feasible, environmentally friendly, renewable, and nonnoxious. Renewable components for biobased plastics corresponding to a large share of the plastics market and epoxidized vegetable oil products can replace many of these. The fatty acids and epoxidized natural-based oils are broadly utilized in manufacturing glycols, polyols, carbonyl combinations, plastic additives for polymers, lubricants, adhesives and cast resins, coatings, and anticorrosion inhibitors, and so on. Currently, there are important search endeavors being undertaken to prepare epoxidized vegetable oil-based plastics in a profitable manner.The literature has numerous scientific publications focusing on the testing and preparation of epoxidized vegetable oil-based plastics. In this paper, we concentrate on epoxidized vegetable oils produced as green plasticizer that have an actual high probability of entering the market or have already accessed the market. © 2023 Scrivener Publishing LLC. All rights reserved.
Keywords: Bioplastic; Epoxidized plant oils; Green material; Multicriteria decision making; Renewable material; Sustainable material